THE SOCIO-DEMOGRAPHIC CORRELATIONS OF PSYCHOLOGICAL CAPITAL - Maria Heitler Lehoczky (European Scientific Journal, ESJ, 2013)
The definition and content of psychological capital is not unitary in the professional literature. Research carried out in this subject is directed at exploring cause-result correlations between certain personal psychological constructs and one of the aspects of labour productivity. In our research the positive, psychology based concept of Psychological Capital (PsyCap) defined by Luthans et al (2007a) is used. This concept consists of four components: self-efficacy, optimism, hope and resiliency which are measured by the Psychological Capital Questionnaire (PsyCap) invented by them.The present paper is a pilot study using the Psychological Capital Questionnaire for the first time in Hungary. Within its framework the Psychological capital questionnaire is applied for the job starters with a business qualification in higher education by examining the socio-demographic correlations (gender, studies, labour market characteristics). The main constraints of the examination are the cross-section layout of the research and few elements in the sample, which limit our cause and effect conclusions. On the basis of the significant results Psychological Capital is considered to determine success in finding a job, earning a good salary and being satisfied with the career alike when employing job starting graduates with a business qualification at the beginning of their career in the labour market.